Revisiting the "New Directions" Report - Colgan, Charles (Maine Policy Review, 1993)
This article is based on a presentation at the Pure '93 Conference last January. Charles Colgan discusses Maine's recent policies on telecommunication. Colgan, former state economist, provided the staff support for Governor Joseph Brennan's report "New Directions in Telecommunications Policy." The analysis of telecommunications policies of the two recent Maine gubernatorial administrations [Brennan and McKernan] reveals a surprisingly common core over the entire period since the AT&T divestiture.
Keywords: Maine; telecommunications policy